PROPHYLAXIS OF VITAMIN AND MINERAL DEFICITS IN CHILDREN - O. V. Stennikova; L. V. Levchuk; N. E. Sannikova (Вопросы современной педиатрии)
Nowadays one of the most pressing problems of prophylactic pediatrics is the provision of children with vitamins and minerals. In the article we review physiological role of calcium, vitamin D and iron, prevalence and clinical presentations of respective deficits in childhood. We also provide with variants of dietary prophylaxis using various products enriched with vitamins and microelements adjusted to average daily norms of calcium, vitamin D and iron consumption.